KOMUNIKASI NONVERBAL PADA MAHASISWI BERCADAR DI UNIVERSITAS IBRAHIMY SITUBONDO - Vindya Wulandari; Mokhammad Baharun (Fakultas Dakwah Universitas Ibrahimy, 2023)
This study discusses nonverbal communication among veiled female students at Ibrahimy Situbondo University. The purpose of this study was to describe the forms of nonverbal communication among veiled female students at Ibrahimy Situbondo University. This research is a qualitative research with a case study type of research. The results of the study found that female students who wore the veil were unable to show their facial expressions, because their faces were covered with the veil cloth used. Even though facial expressions can no longer be seen, veiled female students still show other forms of nonverbal communication that can describe their emotions. That includes gestures, eye communication, touch communication and spatial communication. All of these nonverbal communications can provide meaning and can help expedite the course of the communication process with others.